Long Commute Time and Sleep Problems with Gender Difference in Work-Life Balance: A Cross-sectional Study of More than 25,000 Workers - Soojin Kim; Yangwook Kim; Sung-Shil Lim; Jae-Hong Ryoo; Jin-Ha Yoon (Elsevier, 2019)
Background: There is a lack of statistical analysis investigating the relationship between sleep problems and commute time in Korea. We aimed to analyze the association between representative health symptoms, sleep disturbances, and commute time according to working hours in Korea. Methods: The 4th Korean Working Conditions Survey data were used for analysis, and unpaid family workers and workers who work fewer than three days in a week were excluded. Commute time, working hours, and sleep hours were assessed using self-reported questionnaires. Odds ratios (ORs) with 95% confidence intervals (CIs) for sleep problems were calculated using a multivariate logistic regression model with ≤10 min commute time as the reference group. Results: Among a total of 28,804 workers (men = 14,945, women = 13,859), 2.6% of men and 3.2% of women experienced sleep problems. In both sexes, long commute time (51-60 minutes and >60 minutes) showed an increased OR [men, 2.03 (CI = 1.32-3.13) and 2.05 (CI = 1.33-3.17); women, 1.58 (CI = 1.05-2.39) and 1.63 (CI = 1.06-2.50), respectively]. In stratification analysis of working hours, long commute time (51-60 and > 60 minutes) showed an increased OR in men working >40 hours/week [2.08 (CI = 1.16-3.71) and 1.92 (CI = 1.08-3.41), respectively]. Furthermore, long commute time (41-50, 51-60, and >60 minutes) showed an increased OR in women working >40 hours/week [2.40 (CI = 1.27-4.55), 2.28 (CI = 1.25-4.16), and 2.19 (CI = 1.17-4.16), respectively]. Moreover, commute time >60 minutes showed an increased OR in women working ≤40 hours/week [1.96 (CI = 1.06-3.62)]. Conclusion: This large cross-sectional study highlights that long commute time is related to sleep problems in both sexes. Shorter commute times and decreased working hours are needed to prevent sleep problems in workers. Keywords: Commute time, Sleep problems, Work-life balance, Working hours